2002
DOI: 10.1109/94.983899
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence excitation mechanisms in an epoxy resin under divergent and uniform field

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link: ABSTRACTElectroluminescence excitation mechanisms have been investigated in epoxy resin under divergent and uniform field situations. Metallic wires embedded in the resin were used to produce field divergence whereas film samples were metallised to obtain a uniform field. Electroluminescence under divergent field was stimulated by an impulse voltage. Light was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…These signals show that a positive homocharge peak has developed in the epoxy resin over the time under electrical stress see figure 1. These results are qualitatively the same as those found previously at much higher applied fields (18kV/mm to 180kV/mm) [13]. It seems clear from the position of the peaks and the measurements made during voltage application that the injected charge did not move very far into the epoxy film before being trapped.…”
Section: Homocharge Peakssupporting
confidence: 80%
“…These signals show that a positive homocharge peak has developed in the epoxy resin over the time under electrical stress see figure 1. These results are qualitatively the same as those found previously at much higher applied fields (18kV/mm to 180kV/mm) [13]. It seems clear from the position of the peaks and the measurements made during voltage application that the injected charge did not move very far into the epoxy film before being trapped.…”
Section: Homocharge Peakssupporting
confidence: 80%
“…Above this threshold, the I -E variations could be fitted as well by an E 4 law as by an exponential dependence in sinh(eEλ/2kT ) corresponding to charge hopping between neutral traps at distance λ. In [2], 1 h charging and discharging currents at ambient temperatures have been reported and the transient were attributed to dipole orientation. Lovell [3] reported transient and steady-state currents measured at various temperatures below T g .…”
Section: Introductionmentioning
confidence: 99%
“…Several literature reports support homocharge injection in epoxy resins. Bipolar injection combined to slow polarization has been reported by Griseri et al (2002) in a somewhat different epoxy resin. Iizuka et al (1999) have reported similar behaviour in an epoxy resin, with some effect of relative humidity.…”
Section: Discussionmentioning
confidence: 91%
“…Published reports focussed on the effect of partial discharges and electrical treeing Dodd 1995, Champion et al 1996), but there is comparatively scarce data on the possible influence of internal space charges generated by the thermo-electric stress itself (Guillermin et al 2004, Griseri et al 2002, Iisuka et al 1999. Conclusions of these investigations converge towards consistent results, picturing essentially injection of homocharge close to the electrodes.…”
Section: Introductionmentioning
confidence: 99%